2016
DOI: 10.1017/s003329171500286x
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood characteristics and the incidence of first-episode psychosis and duration of untreated psychosis

Abstract: The incidence of psychotic disorders is related to neighbourhood factors and it may be useful to consider neighbourhood factors when allocating resources for early intervention services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 38 publications
8
63
2
3
Order By: Relevance
“…This problem persists in regard to similar studies of adulthood psychiatric outcomes 10, 13, 15, 17, 18, 19. In contrast, our prospective longitudinal design enabled us to gain traction on the temporal relation between exposure and outcome, thus minimizing the likelihood that our results were due to reverse causation or recall bias.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This problem persists in regard to similar studies of adulthood psychiatric outcomes 10, 13, 15, 17, 18, 19. In contrast, our prospective longitudinal design enabled us to gain traction on the temporal relation between exposure and outcome, thus minimizing the likelihood that our results were due to reverse causation or recall bias.…”
Section: Discussionmentioning
confidence: 95%
“…These findings echo studies of adults that have shown that rates of clinical disorders such as schizophrenia9, 10, 11 and depression12, 13, 14, 15 are higher in more deprived environments. In adults, other aspects of the social environment (i.e., beyond deprivation) including low levels of social cohesion (i.e., the set of shared norms, trust, and networks within a community 16 ) have been linked to schizophrenia10, 17, 18, 19 and depression risk 15, 20, 21, 22, 23. Studies also have shown that individuals with schizophrenia report greater cumulative lifetime exposure to social disadvantage (e.g., having lower levels of education and employment, experiencing greater social isolation, living in more deprived environments) compared with general population controls 24 .…”
mentioning
confidence: 99%
“…This idea was also used in other previous studies (Addington et al, ; Qin et al, ; Ran et al, ). Moreover, some studies found median DUP of 2 months (Kalla et al, ; Qiu et al, ; Schimmelmann et al, ), and 4 months (O'Donoghue et al, ); while other studies dichotomized DUP using the cut‐off point of 3 (Cotter, Zabel, French, & Yung, ; Devi Thakoor et al, ; González‐Valderrama et al, ). Thus, the cut‐off points of 2, 3, and 4 months were also considered in this study in order to see if results could be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…All instruments have known psychometric properties and their use in the cohort have been reported elsewhere (Lyne et al, ; O'Donoghue et al, ; Renwick et al, ). Descriptive statistics were summarized using percentages, means and standard deviations and interquartile range with median where appropriate.…”
Section: Methodsmentioning
confidence: 99%